Recurrence of Papillary Thyroid Carcinoma Associated with Mucoepidermoid Carcinoma: An Uncommon Case Report (Bangladesh Journal of Nuclear Medicine, 2024)
Mucoepidermoid carcinoma (MEC) is most usually found in the salivary glands, but it has also been reported in the lung, esophagus, breast, pancreas, and thyroid. MECs are considered to be low-grade carcinomas, and their occurrence in the thyroid is extremely rare. A case report of a patient with the dual pathology of a composite mucoepidermoid carcinoma of the thyroid and a papillary thyroid carcinoma is presented in this study. A 38-year-old female patient was referred to NINMAS for a 131I whole body iodine scan (DxWBS) with the complaint of big swelling on the right side of the neck and a discharging sinus. She was diagnosed with papillary thyroid carcinoma (PTC) in 2001 after a total thyroidectomy. Comprehensive neck dissection on the right side with left-sided selective neck dissection was done in 2020. Histopathology revealed metastatic papillary thyroid carcinoma on the left side and mucoepidermoid carcinoma on the right side. The patient did not take any RAIT. After a short period of time, the patient started developing a huge neck mass with a discharging sinus. An ultrasonogram of the mass showed a large, heterogeneous mass with microcalcification on the right side of the neck. Biochemical reports revealed a serum thyroglobulin (Tg) level of >300 ng/mL. DxWBS showed a big area of iodine concentration on the right side of the neck. Excision of mass with a skin flap was done in 2022. She received 20cGy fractions of radiotherapy at the right neck. The patient received 131I radioactive iodine therapy at 150 mCi in 2023. The patient is now very ill, with weakness of both lower limbs, blurring of vision, and a diagnosed brain metastasis as well.Bangladesh J. Nuclear Med. 26(2): 204-209, 2023